Binaral rivalry between the nostrils and in the cortex - Zhou, Wen (2009)
When two different images are presented to the two eyes, we perceive alternations between seeing one image and seeing the other. Termed binocular rivalry, this visual phenomenon has been known for over a century [1], and has in recent years been systematically studied at both the behavioral and neural levels [2]. Similar phenomenon has been documented in audition [3]. Here we report the discovery of alternating olfactory percepts when two different odorants are presented to the two nostrils. This binaral rivalry involves both cortical and peripheral (olfactory receptor) adaptations. Our discovery opens up new avenues to explore the workings of the olfactory system and olfactory awareness.